Perception of Benefits, Perception of Easy Used, Attitude and Social Influence on Intention to Use Electronic Medical Records - MHD. Parlindungan; Pamungkas, Rian Adi; Hasyim, Hasyim (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: This research is based on the Karawang Hospital management plan to implement electronic medical records as a whole by the end of 2023. Objective: The aim of this research is to describe perceived benefits, perceived convenience, attitudes and social influences on interest in using electronic medical records. Method: Descriptive studies are used in this research to explain the description of each research variable. The sample in this study was 210 potential users of electronic medical records. The sampling technique was carried out using a non-probability sampling technique, namely a purposive sampling technique. The data collection technique uses a questionnaire. Result: The results found that perceived convenience, attitudes and social influence contribute strongly to increasing interest in using RME. Perceived benefits and perceived convenience can influence attitudes. Perceived benefits, perceived convenience, and attitudes can influence interest in using RME, while social influence has no effect. Intervention attitudes positively influence perceived benefits and perceived convenience, as well as social influences positively interact with the influence of perceived benefits on interest in using RME, while on the influence of perceived convenience on interest in using RME, social influences interact negatively. Conclusion: The study underscores that fostering positive user attitudes and ensuring ease of use are pivotal determinants of successful electronic medical record (EMR) adoption, thereby highlighting the importance of user-centered strategies in EMR implementation. Recommendation: These findings suggest that enhancing positive user attitudes and simplifying EMR use are key drivers in supporting EMR implementation